i-Salman Application: Enhancing Knowledge and Clinical Experience in Health Students - Dwie Yunita Baska; Farida Esmianti; Wewet Savitri; Diah Eka Nugraheni; Sri Nengsi Destriani (Politeknik Kesehatan Kemenkes Mamuju, 2025)
The rapid advancement of technology and the growing demand for improving the quality of healthcare resources have become significant concerns. The iSalman application was developed to support students in enhancing their learning capabilities. This study aimed to examine the effect of the iSalman application on students' knowledge, clinical experience, and competency test outcomes. A quantitative study with a quasi-experimental design (one-group pre-test and post-test) was conducted from January to October 2023. A total of 257 students from the midwifery and nursing study programs were selected using purposive total sampling. The results showed a statistically significant positive correlation between the use of the iSalman mobile application and clinical experience (r = 0.672, p < 0.001). Furthermore, 99.2% of the students were found to be competent based on the competency test results. The iSalman application is effective in improving students' capabilities and has the potential to increase users’ confidence during competency evaluations. Future research should involve a broader range of participants and explore additional application features.